Factors influencing m-retail adoption in India – a comparison between Generation X and Generation Y - Dutta, Prerona (2018)
With the increasing development of wireless mobile technologies and various mobile based applications, it is no doubt that mobile retail activities in India are becoming more popular day by day. However, despite the increasing number of mobile retail users in India, there has been very few studies by the academic researchers in the field of mobile commerce or specifically in the adoption of mobile retail. Therefore, this dissertation attempts to bridge this gap and examine the factors influencing adoption of mobile retail in India, specifically comparing the differences in mobile retail adoption factors among Generation X and Generation Y Indian consumers. The research study involves a set of hypotheses which were built on the foundations of Technology Acceptance Model (TAM) developed by Davis (1989). This theory helped to generate variable constructs for the questionnaire and the required data was collected using collected using convenience sampling approach. A multiple regression analysis was conducted to determine the relationship between the proposed variables. The findings revealed the positive influence of perceived usefulness, perceived ease of use, social influence, trust and perceived risk factors of Generation Y consumers towards m-retail adoption. Meanwhile, the results for Generation X consumers indicated significance of mobility factor along with perceived risk and trust towards the adoption of mobile retail.